The Analysis Of Stroke Patient’s Quality Of Life Based On Response Time In The Emergency Department - Basuni, Hikmah Lia; Saifurrahman, Saifurrahman (Poltekkes Kemenkes Kupang, 2022)
Background: Stroke is a neurological emergency condition that requires immediate treatment. Response time in the emergency room is the initial stage of patient handling in an effort to prevent death and disability. Disability caused in stroke patients is one of the factors that affect the patient's quality of life. This study aims to analysis of stroke patient’s quality of life based on response time in the emergency department. Methods: This study used the Cross Sectional method. The population in this study was all stroke patients who visited the emergency department of Dr. R. Soedjono Selong Hospital with a total sample of 50 patients. The quality of life of patients was measured by EuroQol with good and bad categories, Response time was categorized into fast and slow, data were analyzed using Chi Square test. Results: The sexes of the respondents were male (42%), female (58%) with a dominant age of 51-60 years (26%). The onset of attacks in the morning (58%), the average response time in the emergency room was 134 minutes with the fast category (88%). The average quality of life is 9.22 in the poor category (82%). Chi Square test showed p value 0.111 > 0.05, which means that there is no relationship between response time and the quality of life of stroke patients. Conclusion: Knowledge and understanding of early stroke symptoms is important for the community to prevent delays in patients being taken to health facilities which have an impact on the delay time in handling stroke patients. The availability of Computerized Tomography Scan (CT Scan) in health care facilities is highly recommended to support the advanced management of stroke patients. Latar Belakang: Stroke merupakan keadaan darurat neurologi yang memerlukan penanganan segera. Waktu tanggap di ruang IGD merupakan tahap awal penanganan pasien dalam upaya mencegah kematian dan kecacatan. Kecacatan yang di timbulkan pada pasien stroke menjadi salah satu faktor yang mempengaruhi kualitas hidup pasien. Tujuan penelitian ini menganalisis kualitas hidup pasien Stroke berdasarkan waktu tanggap di IGD. Metode: Penelitian ini menggunakan metode Cross Sectional. Populasi dari penelitian ini adalah semua penderita stroke yang berkunjung ke IGD RSUD Dr.R. Soedjono Selong dengan total sampel 50 pasien, kualitas hidup pasien di ukur dengan EuroQol dengan katagori baik dan tidak baik, Respon time dikategorikan menjadi cepat dan lambat, data di analisis menggunakan uji Chi Square. Hasil: Jenis kelamin responden laki-laki (42%), perempuan (58%) dengan usia dominan 51-60 tahun (26%). Timbulnya serangan pada waktu pagi (58%), rata-rata waktu tanggap di ruang emergensi 134 menit dengan kategori cepat (88%). Kualitas hidup rata-rata 9,22 pada kategori tidak baik (82%). Uji Chi Square dengan p value 0,111 > 0,05 yang berarti tidak ada hubungan waktu tanggap dengan kualitas hidup pasien stroke. Kesimpulan: Pengetahuan dan pemahaman tentang gejala dini Stroke penting diberikan bagi masyarakat guna mencegah keterlambatan pasien dibawa kefasilitas kesehatan yang berdampak terhadap delay time penanganan pasien stroke. Ketersediaan Computerize Tomography Scan (CT Scan) pada fasilitas pelayanan kesehatan sangat di sarankan untuk menunjang penatalaksanaan lanjut pasien Stroke.